Literature Review: Pengembangan Obat Herbal Sebagai Agen Antifertilitas Non Fisik - Agung Ayu Indira Aiswari Utara, Anak (Journal of Comprehensive Science, 2025)
Herbal medicines, containing active plant ingredients, offer an accessible and affordable option as non-physical antifertility agents. Non-physical antifertility agents are substances or methods that prevent pregnancy without requiring physical intervention such as surgery or mechanical contraceptive devices. The research method was carried out by collecting data from ScienceDirect using the keywords "plant AND antifertility", in 2019-2024, 507 scientific articles were obtained. The scientific article used is a Research Article. Of the 75 journals, 9 journals were obtained that met inclusion. The results of this review show that plants that have the potential for developing herbal medicines as non-physical antifertility agents are Helichrysum caespititium, Bulbine frutescens, Teucrium trifidum, Cynodon dactylon, Tamarindus indica, Asparagus africanus, Carica papaya, Azadirachta indica, Adenopus breviflorus, Persicaria hydropiper (L.), and Moringa oleifera. The antifertility properties of some plants are associated with the presence of several phytoconstituent compounds that can inhibit implantation. The conclusion shows that there is great potential for the use of herbal ingredients as non-physical antifertility agents. Some plants and natural ingredients contain compounds that can interfere with the reproductive process. The implications of this review can be used as a reference for further research regarding herbal plants that have potential as non-physical antifertility agents.